An alternative Ultrasonic TimeofFlight Diffraction (TOFD) method. (December 2018) - Yeh, F.W.T.; Lukomski, T.; Haag, J.; Clarke, T.; Stepinski, T.; Strohaecker, T.R.
Abstract: In this work an alternative TOFD method is presented, capable to detect and size defects in the inspected material with good precision. It was shown that the diffraction used in this technique is the most relevant signal among the longitudinal backwall and the shear backwall echoes, compared to other TOFD methods. The proposed technique showed to be particularly efficient in cases where the coventional TOFD method does not perform well; cases include near-surface defects, cracks under compressive stress and bottom tip of defects. The test configuration and a mathematical description referred to the wave path of the signal of interest is described and confirmed by numerical simulations and dynamic and static tests. The proposed method was tested for different defect depth location and find industrial applications such as inspection of cracks in tubes, closed cracks and weld joints. It opens a new possibility for TOFD based inspections.